Recurrence of Minimal Change Disease Following a Motor Vehicle Trauma: An Atypical Cause and Review of Literature - Jayaramakrishna Depa; George Coritsidis (Journal of Trauma and Injury)
Minimal change disease (MCD) in children has a favorable long-term prognosis, and development of end-stage renal disease is very uncommon; less than 5%. In the first case of its kind, we report a 21-year-old female with a history of MCD at the age of 6, who had late relapse subsequent to a motorcycle accident resulting in a de-gloving skin injury and intensive care unit admission. MCD was confirmed by normal light microscopy, podocyte effacement on electron microscopy and absence of any deposits on immunofluorescence 3 weeks after the incident due to critical illness. It is postulated that the skin injury is what caused the relapse of MCD.